National Solid Waste Management Programs and Policies in the City of Bujumbura - Ngabirano, Emmanuel; Ndih, Jean Nke; Bigumandondera, Patrice; Nsengiyumva, Venerand; Manirambona, Jean Bosco; Ntavuna, Marc Nyamugabo (European Scientific Journal, ESJ, 2026)
Solid waste management is a major environmental challenge in Bujumbura City, where rapid growth, low public awareness, and inadequate infrastructure contribute to persistent unsanitary conditions. The objectives of this article are to analyse the evolution of national and municipal solid waste management policies, describe the main programs implemented since the 1980s, and identify the social, institutional, and environmental constraints that limit their effectiveness. A qualitative methodological approach was adopted, combining documentary analysis, institutional reports, participant observation, semi-structured interviews and focus group discussions. We conducted sixty interviews and two focus groups. The main obstacles identified include weak institutional capacity, lack of coordination, lack of sorting at source, low community ownership, and the persistence of informal dumps. The study concludes that sustainable progress requires increased awareness, improved collection infrastructure, the creation of a sanitary landfill, and more consistent environmental governance.